2013
DOI: 10.1038/ncomms3529
|View full text |Cite
|
Sign up to set email alerts
|

Substrate ectodomain is critical for substrate preference and inhibition of γ-secretase

Abstract: Understanding the substrate recognition mechanism of γ-secretase is a key step for establishing substrate-specific inhibition of amyloid β-protein (Aβ) production. However, it is widely believed that γ-secretase is a promiscuous protease and that its substrate-specific inhibition is elusive. Here we show that γ-secretase distinguishes the ectodomain length of substrates and preferentially captures and cleaves substrates containing a short ectodomain. We also show that a subset of peptides containing the CDCYCx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…Indeed, K m values of ≤1 μM have been reported for APP-, APLP-, ErbB4-, and N-cadheren-based substrates as well as notch (44,56,57). This apparently strong interaction between substrate TMD and γ-secretase is in stark contrast to the binding between rhomboid and its substrate, where no physiologically relevant binding affinity between the two is observed.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Indeed, K m values of ≤1 μM have been reported for APP-, APLP-, ErbB4-, and N-cadheren-based substrates as well as notch (44,56,57). This apparently strong interaction between substrate TMD and γ-secretase is in stark contrast to the binding between rhomboid and its substrate, where no physiologically relevant binding affinity between the two is observed.…”
Section: Discussionmentioning
confidence: 56%
“…We find that γ-secretase preferentially cleaves V1711 over dE notch, which has a longer ectodomain by only 13 amino acids. Similarly, the shorter ectodomain α-secretasegenerated C83 fragment of APP is reported to be a better substrate than the longer β-secretase-generated C99 fragment (44). Like APP, the ectodomains of many other γ-secretase substrates can be cleaved at distinct sites by either α-or β-secretase (12,64,65), resulting in different neo-ectodomain lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, Notch TM -Gal4p cleavage consistently produced 5-fold more ␤-galactosidase than did APP C55 -Gal4p, suggesting that Notch was cleaved at a higher efficiency than that of APP in yeast. It has been shown that ␥-secretase easily captures a short extracellular domain of Notch but has decreased interaction with the long extracellular domain of APP C55 (54). Therefore, a substrate-specific effect of these mutations may be due to substrate preference.…”
Section: Discussionmentioning
confidence: 99%
“…A␤42 and A␤40 are produced from the cleavage of APP by the ␥-secretase at the Ala713 and Val711 residues, respectively. The previous experiment [15] reported that the production of A␤42 and A␤40 peptides is prevented by binding some peptides to the cleavage site of APP by the ␥-secretase.…”
Section: Introductionmentioning
confidence: 97%